The physics and dynamics of selected dust storms in the EMM primary mission - Claus Gebhardt; Bijay K. Guha; Roland M. B. Young; Michael J. Wolff; Christopher S. Edwards (2023)
Mars dust storms are an interdisciplinary field of research. They impact the entry-descent-landing operations of spacecraft, the energy production by the solar panels of Mars rovers and landers, and others. As can be foreseen, dust storms are also critical for the future human exploration of Mars. Dust storm research is directly aligned with the Emirates Mars Mission (EMM) science objective on the lower atmosphere, and with the science objective of correlating the lower and upper atmosphere [1,2]. First results of EMM dust storm research were reported in [3].EMM has a high-altitude orbit and provides data products for studies of the Mars atmosphere and surface with a near-hemispheric view. Moreover, EMM can provide information on dust storm activity every few hours or less. EMM observed multiple dust storms during the primary mission, including a large regional dust storm in Sep. and Oct. 2022.The focus of this presentation are unique dust storm observations by the EMM camera EXI [4]. We study a subset of dust storms, which is of particular interest to our research. The formation and growth of dust storms is followed at a (sub-)hourly time scale. This includes results on the dust storm morphology, wind direction, wind speed, surface dust lifting, etc.. Based on that, the implications for the physics and dynamics of dust storms are considered.[1] Amiri, H.E.S., Brain, D., Sharaf, O. et al. The Emirates Mars Mission. Space Sci Rev 218, 4 (2022). https://doi.org/10.1007/s11214-021-00868-x[2] Almatroushi, H., AlMazmi, H., AlMheiri, N. et al. Emirates Mars Mission Characterization of Mars Atmosphere Dynamics and Processes. Space Sci Rev 217, 89 (2021). https://doi.org/10.1007/s11214-021-00851-6[3] Gebhardt, C., Guha, B. K., Young, R. M. B., & Wolff, M. J. (2022). A frontal dust storm in the northern hemisphere at solar longitude 97—An unusual observation by the Emirates Mars mission. Geophysical Research Letters, 49, e2022GL099528. https://doi.org/10.1029/2022GL099528[4] Jones, A.R., Wolff, M., Alshamsi, M. et al. The Emirates Exploration Imager (EXI) Instrument on the Emirates Mars Mission (EMM) Hope Mission. Space Sci Rev 217, 81 (2021). https://doi.org/10.1007/s11214-021-00852-5